Hypercrosslinking porous polymer layers on TiO2-graphene photocatalyst: Enhanced adsorption of water pollutants for efficient degradation. (1st December 2022) - Cai, Zhongjie; Hu, Xiantao; Li, Zhong'an; He, Huijie; Li, Tao; Yuan, Hong; Zhang, Yanrong; Tan, Bien; Wang, Jingyu
Abstract: Solar-driven photocatalysis offers an environmentally friendly and sustainable approach for the degradation of organic pollutants in water without chemical additives, but the low specific surface area and adsorption capacity of common photocatalysts restricts the surface reactions with the contaminants. Herein, we hypercrosslinked polymer layers on TiO2 -graphene surface to enlarge the specific surface area from 136 to 988 m 2 /g, leading to a high adsorption capacity of sulfadiazine as 54.3 mg/g, which is 15.5 times that of TiO2 -graphene (3.5 mg/g). The adsorption kinetics reveals the combination of physical and chemical adsorption by porous benzene-based polymer for sulfadiazine enrichment. Besides, the polymer layers with broad light absorption enable the composite to function efficiently as visible-light-driven photocatalysts. Thus, the as-designed composite exhibits excellent performance for sulfadiazine removal by integrating the adsorptive and photocatalytic processes, especially for the diluted sulfadiazine solution. More importantly, the porous polymer layer can function as a filter for weakening the interference of TiO2 surface with the natural matters from complex water matrices. Based on the identification of dominant reactive species, the possible attacking pathway and the sulfadiazine subsequent degradation are presented. Further, the enhanced adsorption and photodegradation efficiency can also be achieved for the removal of other typical pollutants such as 4-chlorophenol and methylene blue. This study highlights an adsorption-enhanced-degradation mechanism for water pollutants that can direct the design of high-performance photocatalysts under visible light. Graphical abstract: Image, graphical abstract